Indonesian students’ perceptions of mnemonics strategies to recognize Japanese kanji characters - Rasiban, Linna Meilia; Sudana, Dadang; Sutedi, Dedi (Universitas Pendidikan Indonesia, 2019)
ABSTRACTThe purpose of this study is to explore university studentsâ€™ perceptions of the effectiveness of recognizing Japanese Kanji characters by using mnemonic strategies and of understanding Kanjiâ€™s meanings. Fifty Indonesian university students majoring in Japanese Language Education participated in this study. Data were collected through an online questionnaire survey and an in-depth interview with Japanese as a foreign language (JFL) students. Drawing on the analysis of questionnaire and interview data, students reported that the use of mnemonic strategies successfully enhanced their comprehension of Japanese Kanji characters lexically and semantically. The ï¬ndings also showed that the mnemonic strategy was so applicable that students could recognize Japanese Kanji characters. The use of technology also mediated the adoption of the mnemonic strategy. Thus, the implication of the study is that by using different mnemonic strategies along with the use of technology, Japanese teachers could teach Japanese Kanji characters to students whose writing systems background is other than Latin/Roman alphabet systems.